Comparative study of IgA VH3 gene usage in healthy TST− and TST+ population exposed to tuberculosis: deep sequencing analysis. Issue 2 (February 2015) - Chin, Siang Tean; Ignatius, Joshua; Suraiya, Siti; Tye, Gee Jun; Sarmiento, Maria E.; Acosta, Armando; Norazmi, Mohd Nor; Lim, Theam Soon
Summary The acquired immune response against tuberculosis is commonly associated with T‐cell responses with little known about the role of B cells or antibodies. There have been suggestions that B cells and humoral immunity can modulate the immune response to Mycobacterium tuberculosis. However, the mechanisms involving B‐cell responses in M. tuberculosis are not fully understood, in particular the antibody gene preferences. We hypothesized that a preferential use of V genes can be seen associated with resistance to infection mainly in the IgA isotype, which is of prominent importance for infection by pathogens via the mucosal route. We studied healthy individuals with long‐term exposure to tuberculosis, infected (TST+) and uninfected TST−) with M. tuberculosis. From a total of 22 V genes analysed, the TST− population preferred the VH3‐23 and Vκ1 genes. The VH3‐23 genes were subsequently subjected to 454 amplicon sequencing. The TST− population showed a higher frequency of the D3‐10 segment compared with the D3‐22 segment for the TST+ population. The J segment usage pattern was similar for both populations with J4 segment being used the most. A preferential pairing of J4 segments to D3‐3 was seen for the TST− population. The antibodyome difference between both populations suggests a preference for antibodies with VH3‐23, D3‐3, JH4 gene usage by the TST− population that could be associated with resistance to infection with M. tuberculosis.